تعزيز الشراكة بين المدارس والجامعات في المملكة العربية السعودية في ضوء رؤية 2030 من وجهة نظر الخبراء التربويين - الأحمد، هند بنت محمد بن عبدالله (جامعة الطائف, 2020)
استهدفت الدراسة الكشف عن واقع الشراكة بين المدارس والجامعات في المملكة العربية السعودية، وتحديد معوقات ومتطلبات تعزيز الشراكة بين المدارس والجامعات في المملكة العربية السعودية في ضوء رؤية ٢٠٣٠ من وجهة نظر الخبراء التربويين، والتوصل إلى الخيارات الأكثر ملائمة لمجالات تعزيز الشراكة بين المدارس والجامعات في المملكة العربية السعودية في ضوء رؤية ٢٠٣٠ من وجهة نظر الخبراء التربويين: التدريس، البحث العلمي، خدمة المجتمع. ولتحقيق هذه الأهداف استخدمت الدراسة المنهج الوصفي التحليلي والمنهج المستقبلي من خلال أسلوب دلفي، مستعينة بأداة الاستبانة التي طبقت على مجموعة الخبراء التربويين من أعضاء هيئة التدريس بكليات التربية والقيادات في ست جامعات سعودية. وتوصلت الدراسة إلى العديد من النتائج، في جانبيها النظري والميداني، منها: وجود قصور في واقع الشراكة بين المدارس والجامعات في المملكة العربية السعودية وإلى فجوة بين التعليم العام والعالي، وخلصت جولات دلفي الثلاث إلى أن هناك تجانس كبير بين آراء خبراء التربية في جولتي أسلوب دلفي الثانية والثالثة حول درجة موافقة/ مستوى أهمية عبارات معوقات ومتطلبات تعزيز الشراكة بين المدارس والجامعات في المملكة العربية السعودية، وكذلك الخيارات الأكثر ملائمة لمجالات تعزيز بين المدارس والجامعات في المملكة العربية السعودية في ضوء رؤية ٢٠٣٠: التدريس، البحث العلمي، خدمة المجتمع والبالغة (٧٤) عبارة؛ حيث كانت بدرجة كبيرة.
This study aimed at revealing the reality of partnership between schools and universities in the Kingdom and identifying the obstacles and requirements of strengthening the partnership between schools and universities in Kingdom in the light 2030 Vision from education experts’ point of view. The study also aimed at reaching the most appropriate options of the areas of strengthening the partnership between schools and universities in Kingdom in the light 2030 Vision from education experts’ point of View: teaching, scientific research, and community service. To this end, the researcher has used the descriptive analytical approach and future approach through Delphi method, drawing on the questionnaire tool, which has been applied to education experts’ group of teaching staff at Education Colleges and leaders in six (6) Saudi universities. The study found many results in both its theoretical and field aspects, including; there is a deficiency in the reality of partnership between schools and universities in Kingdom as well as a gap between the public and higher education. Delphi three rounds concluded that there is a great homogeneity between education experts’ views in the two rounds of Delphi Method; the second and the third about the degree of compatibility/ level of importance of phrases of obstacles and requirements of strengthening the partnership between schools and universities in Kingdom as well as the most appropriate options of the areas of strengthening the partnership between schools and universities in Kingdom in the light of 2030 Vision: teaching, scientific research, and community service; (74) phrases were in a high degree.
Keywords: الإدارة المدرسية -- الجودة الشاملة -- الخبراء التربوبين -- التعليم الجامعي -- السعودية